Analysis of the lubrication approximation theory in the calendering/sheeting process of upper convected Jeffery's material. (April 2021) - Zahid, M; Khan, NZ; Siddiqui, AM; Iqbal, S; Muhammad, A; Tlili, Iskander
This paper analyses an isothermal calendering for an upper convected Jeffery's Material. Lubrication Approximation Theory (LAT) is applied to simplify the flow equations. Analytical solutions of velocity, flow rate, and pressure gradient are carried out. Outcomes of sheet thickness, detachment point, roll separating force, power input to the roll, and pressure distribution are obtained. The effects of some involved parameters are displayed through graphs and tables. It is noted that the material parameter is a controlling device for sheet thickness, flow rate, detachment point, roll separating force, power input, and the pressure distribution. We observed that as the material parameter increases, the detachment point increases which results in increased sheet thickness.